Dexmedetomidine in Current Anaesthesia Practice- A Review - Naaz, Shagufta (J Clin Diagn Res, 2014)
Dexmedetomidine is an alpha 2 adrenergic receptor agonist, even ten times more selective than clonidine. It is a very versatile drug in anaesthesia practice, finding place in increasing number of clinical scenarios and is no more limited to intensive care unit (ICU) sedation. It is analgesic, has anaesthetic sparing effect, sympatholytic property, useful in other procedural sedation and also has cardiovascular stabilizing property. It reduces delirium and preserves respiratory function which adds benefits to its uses. The aim of this review is to make awareness of its role in present anaesthesia and discuss its limitations at the same time.